Evolution of electromechanical properties of Bi1-xPrxFeO3 solid solutions across the rhombohedral-orthorhombic phase boundary: Role of covalency - Karpinsky, D. V.
Bi1-xPrxFeO3 ceramics of the compositions across the rhombohedral-orthorhombic phase boundary have been studied by X-ray diffraction and piezoresponse force microscopy. Charge density calculations and transport properties measurements have also been performed. Piezoresponse force microscopy measurements revealed a considerable increase of the piezoresponse signal for the x = 0.125 compound with dominant polar rhombohedral phase and minor amount of antipolar orthorhombic phase. Electron density distribution study testified significant increase of covalency of this compound as compared with gradual delocalization of electronic wave functions observed for other Bi1-xPrxFeO3 compounds with higher praseodymium content. Alteration of charge distribution character has been confirmed by resistivity measurements. (C) 2015 Elsevier B.V. All rights reserved.